2000
DOI: 10.1063/1.125643
|View full text |Cite
|
Sign up to set email alerts
|

Blue InGaN-based laser diodes with an emission wavelength of 450 nm

Abstract: Using metal-clad (or plasmonic) waveguide structures in semiconductor lasers carries a promise of reduced size, threshold, and power consumption. This promise is put to a rigorous theoretical test, that takes into account increased waveguide loss, Auger recombination, and Purcell enhancement of spontaneous recombination. The conclusion is that purported benefits of metal waveguides are small to nonexistent for all the band-to-band and intersubband lasers operating from UV to Mid-IR range, with a prominent exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(137 citation statements)
references
References 18 publications
2
135
0
Order By: Relevance
“…These results are in agreement with the experimental results observed previously by Nakamura et al (Nakamura et al, 1998a;Nakamura et al, 2000) in which they studied the laser performance of several laser diodes with an emission wavelength of 390-450 nm as a function of the number of InGaN well layers and found that the lowest threshold current was obtained when the number of InGaN well layers was two.Moreover, in another work they observed that when the number of InGaN well layers of the laser diodes with emission wavelengths longer than 435 nm was varied from one to three, the lowest threshold current was obtained when the number of well layers was one and the threshold current increased when the number of InGaN well layers was increased. This phenomenon was attributed to the dissociation of the high indium content InGaN well layer at a high growth temperature of 750 0C due to a high InGaN dissociation pressure.…”
Section: Wwwintechopencomsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with the experimental results observed previously by Nakamura et al (Nakamura et al, 1998a;Nakamura et al, 2000) in which they studied the laser performance of several laser diodes with an emission wavelength of 390-450 nm as a function of the number of InGaN well layers and found that the lowest threshold current was obtained when the number of InGaN well layers was two.Moreover, in another work they observed that when the number of InGaN well layers of the laser diodes with emission wavelengths longer than 435 nm was varied from one to three, the lowest threshold current was obtained when the number of well layers was one and the threshold current increased when the number of InGaN well layers was increased. This phenomenon was attributed to the dissociation of the high indium content InGaN well layer at a high growth temperature of 750 0C due to a high InGaN dissociation pressure.…”
Section: Wwwintechopencomsupporting
confidence: 92%
“…A maximum output power of 16.6 mW and lowest threshold current of 13.1 m A were obtained when the quantum well number was two. These results are in line with the other experimental results obtained by many researchers (Nakamura et al, 1998b;Nakamura et al, 2000). www.intechopen.com the barriers is increased from 5nm to 9nm the internal field in the barriers is reduced.…”
Section: Ingan/gan Multi Quantum Well Laser Diodesupporting
confidence: 92%
“…In the first generation of commercialized w-LEDs 400 nm blue/violet emission from InGaN quantum wells was mixed with a yellow emission of YAG:Ce phosphor to achieve an impression of a white color [3,4]. This concept (hybrid LED) is still used in recent more efficient w-LEDs.…”
Section: Introduction -Why We Need New Light Sources For Overhead Illmentioning
confidence: 99%
“…Heteroepitaxially grown InGaN-based multiple quantum wells (MQWs) are basic structures for blue and UV laser diodes (LDs) [1,2]. Despite of rapid commercialization of these structures, InGaN-based LDs are still of high cost, have low output power, and relatively short lifetimes.…”
Section: Introductionmentioning
confidence: 99%